Urban regeneration effects on walkability scenarios: An application of space-time assessment for the people-and-climate oriented perspective - Carra, Martina; Rossetti, Silvia; Tiboni, Michela; Vetturi, David (TeMA - Journal of Land Use, Mobility and Environment, 2022)
International programs have shown that implementing people-and-climate oriented cities goes through two processes in physical contexts: (i) urban regeneration of the existing city, particularly on public services for each urban unit, and (ii) planning of their accessibility. Therefore, there is a strong relationship between the goals of people-and-climate oriented and temporal-and-proximity perspectives. Moreover, the Covid-19 pandemic emergency highlighted the relevance of proximity again through the (not new) concept of “15 minutes cities”. Nevertheless, an evaluation of how urban regeneration projects can contribute to achieving sustainability goals in ordinary practice still struggles to consolidate. Consequently, according to both perspectives, this contribution aims to observe and evaluate the effects of local urban regeneration projects on pedestrian mobility. Therefore, it presents a space-time and GIS-based methodology to assess the walkability scenarios in public open spaces. The analysis consists of double temporal analysis: (i) it analyses pedestrian accessibility in a cells grid and through a backtracking algorithm that measures the spatialized isochronous of access time, and (ii) it evaluates accessibility in two temporal moments, ex-ante and ex-post. The assessment framework proposed is applied to the case study of unit Tintoretto tower in Brescia. Results show how urban design produces different space-time effects on pedestrian accessibility and proximity connection within 15 minutes.